Analyzing the Effect of Intensive and Low-Input Agrotechnical Support for the Physiological, Phenometric, and Yield Parameters of Different Maize Hybrids Using Multivariate Statistical Methods. (18th February 2021) - Illes, A.; Bojtor, C.; Szeles, A.; Mousavi, S. M. N.; Toth, B.; Nagy, J.
Abstract : Improving nitrogen efficiency is a crucial strategy for developing sustainable agricultural systems that leads to maximum yield in exchange for minimum inputs and nitrogen loss. Three maize hybrids ( Zea mays L.) of different maturity classes and length of vegetation period (FAO 400, FAO 490, and FAO 380) were selected and for trials during the 2019 growing season. Three different nitrogen (N) fertilization treatments (0, 120, and 305 kg·N·ha −1 ) were applied in order to assess variability in yield-related components. The effect of hybrids, fertilizer, and the interaction of the examined hybrids in relation to fertilizer was significant on yield and oil and protein content. Correlation and biplot analysis show that increases in the lipid peroxidation (LP) amount in the plant leaf stages cause a decrease in the oil content of the harvested yield. The activity of ascorbate peroxidase (APX) and LP at the six-leaf stage directly affects the protein content. The amount of APX at the silking stage has a direct and significant effect on starch content. This study showed that the activity of APX at the silking stage has the highest value in all examined hybrids. APX and LP can be controlled with nitrogen fertilization under various environmental circumstances.